Do external auditors perform a corporate governance role in emerging markets? Evidence from East Asia / Joseph P. H. Fan and T.J. Wong - Fan, Joseph P. H.; Wong, T.J. (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
In emerging markets, the concentration of corporate ownership has created agency conflicts between controlling owners and minority shareholders, which are difficult to mitigate through conventional corporate control mechanisms such as boards of directors and takeovers. This study examines whether external independent auditors could be employed as monitors and as bonding mechanisms to alleviate these agency conflicts. Using a broad sample of firms from eight East Asian economies, we document that firms are more likely to employ Big Five auditors when they are subject to the agency problem imbedded in their ownership structure. In addition, among East Asian auditees subject to the agency problem, Big Five auditors charge a higher fee and set a lower audit modification threshold while non-Big Five auditors do not. Taken together, this evidence suggests that Big Five auditors in emerging markets do have a corporate governance role.